2004
DOI: 10.1074/jbc.m408037200
|View full text |Cite
|
Sign up to set email alerts
|

Construction, Stability, and Activity of Multivalent Circular Anticoagulant Aptamers

Abstract: Here we describe the design and construction of multivalent circular DNA aptamers. Four aptameric binding motifs directed at blood-borne targets are used as a model set from which larger, multidomain aptamers are constructed in a straightforward manner. Intra-or intermolecular ligation of precursor oligonucleotides provides a stabilizing mechanism against degradation by the predominant exonuclease activity of blood products without the need for post-selection chemical modification. In many cases, circular DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
87
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(90 citation statements)
references
References 46 publications
0
87
1
1
Order By: Relevance
“…It has been also shown that engineered aptamers like multivalent circular constructs exhibit increased stability against cleavage by exonucleases and improved (2 to 3-fold) anticoagulant activity in comparison with canonical single stranded aptamers [8]. Increased inhibitory activity against HIV-1 reverse transcriptase has been shown also for recently reported bimodular DNA aptamers [7].…”
Section: Accepted M Manuscriptmentioning
confidence: 78%
See 1 more Smart Citation
“…It has been also shown that engineered aptamers like multivalent circular constructs exhibit increased stability against cleavage by exonucleases and improved (2 to 3-fold) anticoagulant activity in comparison with canonical single stranded aptamers [8]. Increased inhibitory activity against HIV-1 reverse transcriptase has been shown also for recently reported bimodular DNA aptamers [7].…”
Section: Accepted M Manuscriptmentioning
confidence: 78%
“…Nowadays, increased interest in aptamer research is focused on improvement of these features for application in medical therapy, biotechnology and biosensor development [3,4]. A novel approach in aptamer engineering is based on dimerization [5][6][7] or multimerization [8], which possess two or more binding sites for the target ligand. Among DNA aptamers, those sensitive to thrombin are most studied.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been reported to examine the biophysical and chemical properties of the G-quadruplex (Di Giusto and King, 2004;Peng and Damha, 2007;Sacca et al, 2005) and also showed the sensitive nature of the quadruplex upon chemical modification (Marathias et al, 1999;Sacca et al, 2005). The control of the inhibitory function of the aptamer is a challenging aspect.…”
Section: Introductionmentioning
confidence: 98%
“…Firstly, cyclic oligonucleotides can be used to target singlestranded DNA 24,25 and RNA 26 with higher affinity and selectivity than their linear counterparts. Secondly, dumbbells can acts as aptamers 27,28 and transcription factor decoys. 29,30 Finally, small cyclic ribodinucleotides, such as c-di-AMP 31 and c-di-GMP, 32 are important second messenger signaling molecules that regulate many processes in bacteria.…”
Section: Introductionmentioning
confidence: 99%